Magnetic Compass Orientation in a Palaearctic–Indian Night Migrant, the Red-Headed Bunting - Tushar Tyagi; Sanjay Kumar Bhardwaj (Animals, 2021)
Red-headed Buntings (Emberiza bruniceps) perform long-distance migrations within their southerly overwintering grounds and breeding areas in the northern hemisphere. Long-distance migration demands essential orientation mechanisms. The earth’s magnetic field, celestial cues, and memorization of geographical cues en route provide birds with compass knowledge during migration. Birds were tested during spring migration for orientation under natural clear skies, simulated overcast skies at natural day length and temperature, simulated overcast at 22 °C and 38 °C temperatures, and in the deflected (−120°) magnetic field. Under clear skies, the Red-headed Buntings were oriented NNW (north–northwest); simulated overcast testing resulted in a northerly mean direction at local temperatures as well as at 22 °C and 38 °C. The Buntings reacted strongly in favor of the rotated magnetic field under the simulated overcast sky, demonstrating the use of a magnetic compass for migrating in a specific direction.